Comparison of Eye Fatigue Incidence Between Male and Female Medical Students with Refraction Error - Wardana, Made Kusuma; Permatananda, Pande Ayu Naya Kasih; Sedani, Ni Wayan; Cahyawati, Putu Nita; Aryastuti, Anak Agung Sri Agung (Direktorat Penerbitan dan Publikasi Ilmiah, Universitas Surabaya, 2023)
Abstract—Eye fatigue is one of main problems faced by students during their education. The female gender is known to have a higher risk of eyestrain than the male gender. This study was conducted to analyze the differences in eyestrain event of medical students with refractive error based on gender. This research was an analytic observational study with cross-sectional design. Male and female students with refractive errors, aged 18-20 years old, and willing to participate in the study were included. Eyestrain was measured using Visual Fatigue Score questionnaire in Indonesian. Chi Square analysis was carried out to analyze the differences in eyestrain event of medical student with refractive error based on the gender. Results: There were 117 respondents in this study, which consisted of 57 male students and 57 female students, both were with refractive errors. Of the 117 respondents, 62 respondents experienced with eyestrain, with details of 24 were male students and 38 were female students. Chi Square analysis obtained a P value of 0.001 which means significantly different. In addition to refractive errors, gender is another variable that can affect the event of eyestrain in medical students. Prevention efforts need to be done to overcome this problem. Keywords: eye fatigue, gender, refraction error, medical student Abstrak—Kelelahan mata merupakan salah satu masalah utama yang dihadapi mahasiswa selama menjalani pendidikan. Jenis kelamin perempuan diketahui memiliki risiko kelelahan mata yang lebih tinggi daripada jenis kelamin laki-laki. Penelitian ini bertujuan untuk menganalisis perbedaan kejadian kelelahan mata pada mahasiswa kedokteran dengan gangguan refraksi berbasis gender. Penelitian ini merupakan penelitian observasional analitik dengan rancangan cross sectional. Mahasiswa atau mahasiswi kedokteran dengan gangguan refraksi, berusia 18-20 tahun, dan bersedia mengikuti penelitian dimasukkan ke dalam penelitian. Kelelahan mata diukur dengan menggunakan kuesioner Visual Fatigue Score dalam Bahasa Indonesia. Analisis Chi Square dilakukan untuk menganalisis perbedaan kelelahan mata pada mahasiswa dan mahasiswi kedokteran dengan gangguan refraksi. Responden penelitian ini berjumlah 117 yang terdiri dari 57 mahasiswa dan 57 mahasiswi dengan gangguan refraksi. Dari 117 responden tersebut, 62 responden mengalami kelelahan mata, dengan rincian 24 adalah mahasiswa dan 38 adalah mahasiswi. Analisis Chi Square didapatkan nilai p= 0,001 yang berarti bermakna signifikan. Selain gangguan refraksi, gender adalah hal yang dapat berpengaruh pada kejadian kelelahan mata pada mahasiswa. Upaya pencegahan perlu dilakukan untuk dapat mengatasi hal tersebut., Kata kunci: kelelahan mata, gender, gangguan refraksi, mahasiswa kedokteran